Pembiakan Cacing Tanah Perionyx Excavatus Dengan Teknik Vermikultur Limbah Peternakan Dan Pengaruhnya Terhadap Pupuk Kandang Yang Dihasilkan - Yumaihana Yumaihana (Universitas Andalas, 2007)
The life cycle of earthworm Perionyx excavatus in the faces of livestock animals has been studied and had potency to depredate the animal wastes through vermiculture process. Optimal live environmental conditions were needed to achieve the optimal vermiculture process. The rate of growth and reproduction of the worm depended mainly on the availability of nutition in the medium. In this experiment, four different animal feces were used as vermiculture media, e.g. cattle, horse, rabbit and chicken. The increase of body length was measured as the growth rate function of the worm P. excavagatus. The change of temperature, pH and humidity of medium were measured as the factors affecting the growth rate. These factors were important in research objectives, i.e. production of earthworm biomass for poultry feedstuff and of high quality biofertilizer by using animal wastes as vermiculture medium. Feces of cattle and rabbit were found the best medium of vermiculture. P.excavagus cultivated in the feces of both animals showed the fast similar growth rate. The growth rate of P.excavagus in four different medium could be ordered as follows: cattle feces> rabbit feces>horse feces. Feces of chicken was found not suitable for earthworm media because of low pH. Biofertilizer from the vermiculture could be produced in relatively short time period with better physical characteristic in compare to the normal biofertilizer.